Plan de promoción y publicidad para la cuenta de ahorro programado del Banco Internacional sucursal Quevedo, año 2014 - Montes Sud, Ángela María (2015)
The thesis called "Plan of Promotion and Publicity for the Programmed Savings Account at Banco Internacional branch Quevedo" aims to increase the number of customers that currently have this product, through market research and the implementation of strategies for positioning in Quevedo City. In recent years, a stronger financial system combined with higher income levels in the country has opened a market for a percentage of the population to start building savings with the objective to fulfill a personal goal. With the purpose of reaching the target audience the following approached is performed: description, formulation and delimitation of the research that consisted of comparing the expected results with those obtained during the first years of opening this account. Through this work the following hypothesis was formulated “the low participation of the target market is due to the unawareness of the benefits provided by the Programmed Savings Account at Banco Internacional branch Quevedo.” This work includes a review of literature concerning the topic of the study as well as field work that was conducted via surveys to current clients with programmed savings accounts and to those that do not have an account. The results of this research are favorable for both clients that already have this account as those that have not yet open one due to lack of knowledge or lack of motivation. Therefore, it concludes by submitting a proposal that will increase the number of clients for the Programmed Savings Account in the Banco Internacional in the City of Quevedo.